Evaluation of change in biochar properties derived from different feedstock and pyrolysis temperature for environmental and agricultural application - Pariyar, Priya; Kumari, Kanchan; Jain, Manish Kumar; Jadhao, Pradip S. (The Science of the total environment, 2020)
In recent years, the application of biochar has increased significantly for sustainable and efficient carbon sequestration, improving soil quality and enhancement of plant growth. The biochar is mostly made from agricultural residues and waste materials. The objective of this study was to assess the changes in physicochemical, surface morphology, and mineral composition of different biochars with varying pyrolysis temperature. Eighteen different types of biochars were prepared through pyrolysis of feedstock at four different temperatures (350 °C, 450 °C, 550 °C and 650 °C). The feedstock used for the preparation of biochar were organic waste materials such as pine saw dust, rice husk, food waste, poultry litter and paper sludge. Pyrolysis temperatures and feedstock types significantly influenced biochar properties. For instance, pH of poultry litter and paper sludge biochar has increased from 6.2 to 10.3, BET surface area of saw dust and rice husk increased from 3.39 to 443.79 m2 g−1 and 11.61 to 280.97 m2 g−1 while cation exchange capacity value decreased with the increase in temperature. Paper sludge and poultry litter had the highest ash content value (57.20 ± 0.02 and 44.10 ± 0.02) whereas saw dust, rice husk and food waste biochar have highest fixed carbon value (55.31 ± 0.15, 48.47 ± 0.31 and 58.85 ± 0.22) at 650 °C. Degree of aromaticity increased and polarity reduced significantly with pyrolysis temperature. Rice husk and saw dust biochar prepared at higher temperature were more stable among all and thus recalcitrant in nature. X-ray diffraction results revealed mineral like quartz in saw dust and poultry litter biochar, sylvite, potassium iodate, calcium sulfide in food waste biochar and calcium carbonate in paper sludge biochar. Scanning Electron Microscopy showed increase in number of pores as well as pore size specially for the saw dust, and rice husk biochar. This study suggested that biochar prepared at higher temperature (550 °C and 650 °C) are more suitable for carbon sequestration and agricultural purpose. [Display omitted] •Conversion of four different waste feedstocks into biochar with varying temperature.•Higher temperature biochar tends to have half-life greater than that of the lower temperature.•Heavy metals increase with the pyrolysis temperature except metals with low boiling point.•BET surface area significantly increases with the pyrolysis temperature.